Influência do tratamento de superfície em pinos anatômicos na resistência de união ao cimento resinoso autoadesivo - Machry, Renan Vaz (2018)
The aim of the study was to verify the influence of surface treatments on the bond strength of anatomic posts to a self-adhesive resin cement. For the push-out test, 80 bovine teeth were treated endodontically. After 24 hours, the preparation of the post space was performed and the roots were widened with diamond burs. Afterwards, relined glass fiber post with microhybrid composite resin (anatomic posts) obtained through the modeling of root canals were divided into groups according to the applied surface treatment (n = 10): absence of treatment (GC), absence of treatment with silane (GCS), sandblasting with aluminum oxide without (GS) and with silane application (GSS), treatment with 35% hydrogen peroxide without (GP) and with application silane (GPS) and treatment with 10% hydrofluoric acid without (GF) and with silane application (GFS). The posts were cemented to the root canals and, after 24 hours of storage, 1.5mm thick slices were obtained for the push-out test. The bond strength values were obtained in MPa and the failures were classified with a stereomicroscope in adhesive or cohesive, with only the adhesive failure between resin cement and composite resin were considered for statistical analysis. For the microtensile bond strength test (MTBS), were made blocks of microhybrid composite resin. The same surface treatments of the push-out test were randomly distributed to be applied on one of the faces of the blocks. Two blocks with same treatment were cemented together with self-adhesive resin cement. Ten sets of each group were obtained and cutting in a cut machine to obtain 16 sticks per block for the MTBS. Half of the specimens was immediately tested, and another half was subjected to 12,000 cycles of thermocycling and storage for 120 days before the mechanical test (n = 80). The data were tabulated in MPa considering the area of the adhesive interface and the load required to separate the sticks. The failures were classified as adhesive or cohesive. For the push-out test, there was no difference between the groups. In the MTBS the higher bond strength values was obtained for the sandblasted blocks followed by the silane application when in the specimens immediately tested. On the other hand, the use of 10% hydrofluoric acid without silane and 35% hydrogen peroxide with silane showed results significantly lower than the other treatments when compared to those under the same application condition or not the chemical coupling agent. The thermocycling caused a statistically significant decrease in the means of bond strength for all groups, in addition, it was possible to observe higher values in the sandblasted groups without there being any difference with silane application. A sample of each group was prepared for analysis of the surface by scanning electron microscopy, which presented visible differences of surface roughness between the groups. The MTBS’ findings allow to conclude that the sandblasting of the composite resin surface generates an increase in bond strength with the self-adhesive resin cement. However, the interface that presented the greatest number of failures in the push-out test was between resin cement and root dentin.